Hadits Bukhari Pandangan Tentang Perjudian Online dan Implikasinya pada Ayat (2) Pasal 27 UU No. 1 Tahun 1945 - M. Nazki Toriqissalam; Tajul Arifin (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This article examines the prohibition of gambling from the perspective of the Hadith narrated by Bukhari No. 5787 and its relevance to the practice of online gambling in the digital era. The study employs a qualitative approach with descriptive-analytical methods focusing on the analysis of hadith texts and Indonesian positive law, particularly Article 27 Paragraph (2) of Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law). The findings reveal that online gambling has destructive impacts on individual morality, family resilience, and the economic stability of society. Bukhari’s Hadith strictly forbids all forms of gambling, including invitations to gamble, and offers charity as an alternative act of purification. Although Indonesian positive law regulates online gambling prohibition, challenges remain in its effective enforcement. This article highlights the need for a synergistic approach between religious normative values and state law enforcement to address the phenomenon of online gambling comprehensively.